PENGUATAN KESADARAN HUKUM PELAJAR TERHADAP NARKOTIKA SEBAGAI UPAYA PENCEGAHAN DINI DI SEKOLAH - Ahmad Muhaimin Aziz; Rendi Kahfi Septiana; Dadi; Adih Rosadi; Hafiz Wijiarto (PT. Hasba Edukasi Mandiri, 2026)
Narcotics abuse among students is a social and legal issue that requires serious attention. This community service and research aimed to enhance students' legal awareness regarding the dangers of narcotics through socialization activities at SMKN 7 Serang City. The methods used included legal counseling, interactive discussions, and an evaluation of students' understanding. The results showed that most students did not have a comprehensive understanding of the types of narcotics, legal sanctions, and the social and health impacts caused. After the socialization, the students demonstrated an increased awareness of the dangers of narcotics and the importance of avoiding substance abuse. This activity proves that early legal education plays a crucial role in building a culture of legal awareness within the school environment.